Hubungan Sikap Dan Motivasi Belajar Dengan Prestasi Belajar IPS Terpadu Siswa Kelas VIII - Wahyu Bimantara F; Pargito Pargito; Rahma Kurnia Sri Utami (JPG (Jurnal Penelitian Geografi), 2017)
The research aims to find out (1) the relationship between students learning attitude and achievement, (2) the relationship between students learning motivation and achievement, (3) the relationship between students learning attitude and achievement in Integrated Social Studies at 8th grade of SMPN 2 Raman Utara, Lampung Timur, academic year 2015-2016. The research was conducted quantitatively whose research population was the students of 8th grade of SMPN 2 Raman Utara. Research sampling was taken through proportional random sampling with 51 sample. Data was analyzed by Spearman coefficient correlation and multiple correlation. Results of the research show that (1) there is positive relationship between students learning attitude and achievement, (2) there is positive relationship between students learning motivation and achievement, (3) there is positive relationship between students learning attitude, motivation, and achievement in Integrated Social Studies at 8th grade of SMPN 2 N Raman Utara, Lampung Timur, academic year 2015-2016.Penelitian ini bertujuan untuk mengetahui (1) hubungan sikap dengan prestasi belajar, (2) hubungan motivasi dengan prestasi belajar, (3) hubungan sikap dan motivasi dengan prestasi belajar pada mata pelajaran IPS Terpadu siswa kelas VIII di SMPN 2 Raman Utara Lampung Timur tahun ajaran 2015/2016. Jenis penelitian ini adalah penelitian kuantitatif. Populasi penelitian adalah siswa kelas VIII di SMPN 2 Raman Utara. Teknik pengambilan sampel penelitian menggunakan proportional random sampling, dengan jumlam sampel sebanyak 51 siswa. Analisis data penelitian menggunakan koefisien korelasi Spearman dan korelasi ganda. Hasil penelitian menunjukkan bahwa (1) ada hubungan positif antara sikap dengan prestasi belajar,(2) ada hubungan positif antara motivasi dengan prestasi belajar, (3) ada hubungan positif antara sikap dan motivasi belajar dengan prestasi belajar IPS Terpadu siswa kelas VIII di SMPN 2 Raman Utara Lampung Timur tahun ajaran 2015/2016 .Kata kunci: motivasi, prestasi belajar, sikap